Time is running out: Microsatellite data predict the imminent extinction of the boreal lynx (Lynx lynx) in France - Huvier, Nathan; Moyne, Gilles; Kaerle, Cécile; Mouzon-Moyne, Lorane (Frontiers in Conservation Science, 2023)
The Eurasian lynx reappeared in the French Jura Mountains, in the late 1970s, as the result of the dispersion of lynxes from the Carpathian region reintroduced in Switzerland in the early 1970s. Since then, the state of this population has remained poorly known. One estimate gives the number of individuals between 120 and 150. Opportunistic observation and monitoring suggest poor connectivity with the populations in Germany or in other parts of Switzerland. Forty years after its comeback in France, we could expect a higher number of individuals, but possible inbreeding depression as well as threats such as poaching and collisions with cars may explain the limitation of number of individuals observed and may lead to a new extinction of the specie in this region. We used 23 microsatellite markers and 78 DNA samples, collected between 2008 and 2020, to establish the genetic state of the French Jura Mountain lynx population. Our results show extremely low genetic diversity with an observed heterozygosity (Ho) of 0.36 and an effective population size (Ne) of 38.2. When comparing the source population (Carpathian), the inbreeding level is very worrying (Fe = 0.41). These results are among the lowest recorded for the Eurasian lynx. To avoid extinction, which we estimate will occur in approximately 30 years, we recommend the introduction of new genetic material. Although reintroduction is controversial, solutions such as the replacement of poached lynxes and the exchange of orphan lynxes between care centers are good initial actions for population strengthening. This offers a rapid intervention while studying solutions for more sustainable conservation